Greater magnitude of entheseal microdamage and repair in psoriatic arthritis compared with ankylosing spondylitis on ultrasound. (26th September 2018) - Arslan Alhussain, Fatıma; Kasapoglu Gunal, Esen; Kurum, Esra; Bakirci, Sibel; Ozturk, Ayse Bilge; McGonagle, Dennis; Aydin, Sibel Zehra
Abstract: Objectives: AS and PsA share clinical and immunological features centred on enthesitis. However, a strong association between PsA and preceding injury has been recognized. The aim of this study was to test the hypothesis that the entheseal damage seen by US is commoner in PsA patients than in AS patients. Methods: Seventy-nine AS and 85 PsA patients had US scans of 1640 entheses to calculate entheseal inflammation (hypoechogenicity, thickening and Doppler) and damage scores (calcifications, enthesophytes and erosions). Regression modelling was done to evaluate the effect of diagnoses on outcomes, controlling for age, gender, BMI, clinical enthesitis, HLA-B27, and anti-TNF use. Results: Both inflammation and damage scores on US were correlated with BMI ( r = 0.392; r = 0.320) and age ( r = 0.308; r = 0.538) ( P < 0.001), and men had higher inflammation scores than women [12.3 (7.5) vs 8.9 (7.3), P = 0.001]. In multivariate analysis, despite similar (anti-TNF–treated patients) or slightly less inflammation (anti-TNF–naïve patients) in the PsA group, they had 4.22 times more US damage than their counterparts with AS. The difference was even higher in the anti-TNF–naïve patients (5.6 times). Conclusion: On US assessment, PsA patients have greater entheseal insertion damage scores compared with AS, suggesting potential differences in tissue repair, immunobiology or response to injury at insertions.